Impact of Enzyme Replacement Therapy in a Patient Younger Than 2 Years Diagnosed With Maroteaux-Lamy Syndrome (MPS VI) - Guio,Johanna Acosta (2017)
Abstract Introduction: Mucopolysaccharidosis type VI, also known as Maroteaux-Lamy syndrome (#OMIM 253200), is a rare autosomal recessive genetic disorder due to deficient activity of the enzyme N-acetylgalactosamine 4-sulfatase (arylsulfatase B) required for the breakdown of dermatan sulfate and chondroitin sulfate. Patient: Report of a female patient started on enzyme replacement therapy at 17 months of age. At the time of diagnosis (14 months), the patient presented mild corneal opacity and significant thoracolumbar kyphosis, but no visceral involvement or growth arrest. At 73 months of treatment, weight was normal, although the patient was in a low height percentile. The patient showed adequate neural development, with improvement in lumbar spine and joint involvement. Corneal compromise or valvular disease progression was not evident. Conclusion: Early and timely diagnosis and treatment with enzyme replacement therapy are essential, as the means to change the natural history of the disease, avoiding comorbidities and improving final prognosis.